ANALISIS PERTUMBUHAN EKONOMI INKLUSIF : STUDI KOMPARASI ANTAR PROVINSI DI INDONESIA - Afriliana, Shinta Nadia; Wahyudi , Setyo Tri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to analyze inclusive growth in 34 Indonesian provinces and the factors that can support inclusive growth rapidly developing in Indonesia. By using secondary data from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance (DJPK) ranging from 2014 to 2020. This study uses the Poverty Equivalent Growth Rate (PEGR) method and uses a dynamic panel data estimation model using the Generalize Method of Moment Arellano. Bond (GMM – AB). By using three estimation models, namely, the first model focuses on regions that are in quadrants I, II (provinces that have been inclusive, the second model focuses on quadrant III, IV (provinces that are not yet inclusive), and the third model focuses on 34 provinces in Indonesia. Indonesia. With the results of the study showing that economic growth in Indonesia is still not fully inclusive. In this study, per capita income, education expenditure budget, health expenditure budget, and FDI have an influence on the emergence of inclusive growth in Indonesia. While DDI is a variable that does not support the emergence of growth inclusive in Indonesia.